Novel venous balloon for compliance measurement and stent sizing in a post-thrombotic swine model - Wang, Mengjun; Lu, Xiao; Han, Ling; Wang, Amy M.; Raju, Seshadri; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Real-time accurate venous lesion characterization is needed during endovenous interventions for stent deployment. The goal of this study is to validate a novel device for venoplasty sizing and compliance measurements.Methods: A compliance measuring sizing balloon (CMSB) uses real-time electrical conductance measurements based on Ohm's Law to measure the venous size and compliance in conjunction with pressure measurement. The sizing accuracy and repeatability of the CMSB system were performed with phantoms on the bench and in a swine model with an induced post thrombotic (PT) stenosis in the common femoral vein of swine.The accuracy and repeatability of the CMSB system were validated with phantom bench studies of known dimensions in the range of venous diameters. In 9 swine (6 experimental and 3 control animals), the luminal cross-sectional areas (CSA) increased heterogeneously along the PT stenosis when the CMSB system was inflated by stepwise pressures. The PT stenosis showed lower compliance compared to the non-PT vein segments (5 mm 2 vs. 10 mm 2 and 13 mm 2 at a pressure change of 40 cm H2O). Compliance had no statistical difference between venous hypertension (VHT) and Control. Compliance at PT stenosis, however, was significantly smaller than that at Control and VHT (p<0.05, ANOVA).The CMSB system provides accurate, repeatable, real-time measurements of CSA and compliance for assessment of venous lesions to guide interventions. These findings provide the impetus for future first-in-human studies.